Genome dynamics of high-risk resistant and hypervirulent Klebsiella pneumoniae clones in Dhaka, Bangladesh - Hussain, Arif; Mazumder, Razib; Ahmed, Abdullah; Saima, Umme; Phelan, Jody E.; Campino, Susana; Ahmed, Dilruba; Asadulghani, Md; Clark, Taane G.; Mondal, Dinesh (Frontiers in Microbiology, 2023)
Klebsiella pneumoniae is recognized as an urgent public health threat because of the emergence of difficult-to-treat (DTR) strains and hypervirulent clones, resulting in infections with high morbidity and mortality rates. Despite its prominence, little is known about the genomic epidemiology of K. pneumoniae in resource-limited settings like Bangladesh. We sequenced genomes of 32 K. pneumoniae strains isolated from patient samples at the International Center for Diarrhoeal Disease Research, Bangladesh (icddr,b). Genome sequences were examined for their diversity, population structure, resistome, virulome, MLST, O and K antigens and plasmids. Our results revealed the presence of two K. pneumoniae phylogroups, namely KpI (K. pneumoniae) (97%) and KpII (K. quasipneumoniae) (3%). The genomic characterization revealed that 25% (8/32) of isolates were associated with high-risk multidrug-resistant clones, including ST11, ST14, ST15, ST307, ST231 and ST147. The virulome analysis confirmed the presence of six (19%) hypervirulent K. pneumoniae (hvKp) and 26 (81%) classical K. pneumoniae (cKp) strains. The most common ESBL gene identified was blaCTX-M-15 (50%). Around 9% (3/32) isolates exhibited a difficult-to-treat phenotype, harboring carbapenem resistance genes (2 strains harbored blaNDM-5 plus blaOXA-232, one isolate blaOXA-181). The most prevalent O antigen was O1 (56%). The capsular polysaccharides K2, K20, K16 and K62 were enriched in the K. pneumoniae population. This study suggests the circulation of the major international high-risk multidrug-resistant and hypervirulent (hvKp) K. pneumoniae clones in Dhaka, Bangladesh. These findings warrant immediate appropriate interventions, which would otherwise lead to a high burden of untreatable life-threatening infections locally.